Progressive failure analysis of CFRP composite laminates under uniaxial tension using a discrete element method. (April 2021) - Wan, Lei; Ismail, Yaser; Sheng, Yong; Wu, Ke; Yang, Dongmin
This study presents a 3D Discrete Element Method (DEM) model for the progressive failure analysis of Carbon Fiber Reinforced Polymer (CFRP) composite materials subjected to uniaxial tensile loading. Particles in the model are packed and bonded in regular patterns (hexagonal or square). The relationship between the bond stiffness and material properties is established based on the average strain energy method. The random distribution of bond strengths calibrated from experiments with a variation of 30% and 10% following a normal distribution law is assigned to the bonds in 0∘ and 90∘ plies to capture random cracks, respectively. Tsai-Hill failure criterion is utilized for the calibration of bond strength of± 45 ° plies to predict their failures in composite laminates. Quantitative and qualitative analyses were conducted for predicting the damage initiation and propagation of the cross-ply and Quasi-Isotropic (QI) composite laminates under tensile loading, respectively. Two interface stiffnesses were utilized in the failure prediction of cross-ply composite laminates, and it was found that the numerical results with the interface stiffness calculated from fracture energy are in good, quantitative agreements with the experiments. All the four stages of the failure process of QI composite laminates are well captured by the 3D DEM model, including isolated cracks, inner delamination cracks, outer delamination cracks and final failure.